Analysis and Interpretation of Metaphors: Exploring Young Adults' Subjective Experiences With Depression. (July 2021) - Roystonn, Kumarasan; Teh, Wen Lin; Samari, Ellaisha; Cetty, Laxman; Devi, Fiona; Shahwan, Shazana; Chandwani, Nisha; Subramaniam, Mythily
The aim of this study was to provide a cross-cultural exploration of how young adults with depression use metaphors to describe their illness experiences. Data were collected in semi-structured interviews, designed to capture rich and detailed descriptions of participants' firsthand narrative experiences of depression and how they make sense of depression. Thirty-three participant interview data were analyzed, using a combination of deductive and inductive approaches. The analysis resulted in extracting five major themes with sub-themes, which detail the diversity and vividness of metaphorical expressions embedded in participants' accounts and produce insights and a richer picture of the depression experience. Metaphors play a pivotal role in providing a rich resource that young adults rely on, to construct meaningful accounts about their illness. This highlights the importance of a metaphor-enriched perspective in research as well as in clinical practice, particularly in a multicultural health care setting.